Plan de mejora como herramienta en el área de servicio al cliente empresa Surti -Belleza Tunja S.A.S (2022)
The implementation project of an improvement plan as a tool in the area of customer service in the company SURTI BELLEZA S.A.S, is one of the improvement strategies to develop in the company in order to achieve a significant increase in sales; this company dedicated to the area of beauty and personal care through its multiple services and cosmetic products. The area of customer service is understood as the one in charge of the attention and facilitation of the service or product to the consumer in order to bring to its maximum satisfaction; customer service is one of the indispensable tools within the organization, therefore, it is necessary to implement and follow up a good customer service as a business strategy within the organization.